Placer les services climatiques dans les mains des agriculteurs - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the International Research Institute for Climate and Society (IRI), the Earth Institute, Columbia University show the importance of supporting farmers with climate information services in a variable and changing climate. Features sharp animation, farmer interviews and on-the-ground footage from farms and agricultural extension centers in Mali and India. Animation and video production by Skypunch Creative. Footage by Francesco Fiondella, International Research Institute for Climate and Society. Learn more: Putting climate services in farmers' hands blog posting: http://bit.ly/1k2du6h CCAFS Research Theme on Climate Risk Management: https://ccafs.cgiar.org/themes/climate-risk-management CCAFS' work on delivering climate services for farmers: https://ccafs.cgiar.org/climate-services-farmers Expertise in climate and agriculture at the IRI: http://iri.columbia.edu/our-expertise/agriculture/ Footage by Francesco Fiondella, IRI Video by Skypunch Creative: http://skypunchcreative.com/ for the Earth Institute, Columbia University: http://www.earthinstitute.columbia.edu